Marketing - Grewal Dhruv (Mc Graw Hill, 2016)
Grewal and Levy's Marketing is the first text published since the AMA introduced its new value-based definition of the word "Marketing", making it the most modern and forward thinking of all principles of marketing offerings. It seeks to apply the marketing concept. Marketing and its supplementary package was built from scratch by focusing on what the market wants. The motto, "Marketing Creates Value" permeates this text and is stressed through the main themes of entrepreneurship, service global marketing, and ethics. .